2017
DOI: 10.3329/bjms.v16i3.32846
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Skin & Venereal disorders among patients attending in the OPD of Dermatology & Venereology Department of a tertiary care private hospital, Dhaka, Bangladesh.

Abstract: Background :It is generally agreed that pattern of skin & venereal diseases differ in different countries and within various regions of a country depending upon social, economic , racial & environmental factor. The morbidity associated with skin and venereal diseases makes them an important public health problem. Very scanty literature is found on the problem which is either disease based, community based or specified population group based. Objective : To assess the pattern of skin and venereal diseases in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…From the study of Alam, Husain and Quarashi, (2017) it was revealed that 16.2% of patients had total burden of miscellaneous Dermatoses, Eczema (27.7%) And Fungal Infections (11.2%). 9 In the study of Ahmed et al majority of the subjects had acne vulgaris (29.5%), followed by atopic dermatitis (22.3%), vitiligo (20.7%) and psoriasis (6.4%); the remainder had other diseases such as alopecia areata, lichen planus or warts. Reported a prevalence of depression of 18% in 50 Alopecia patients and a prevalence of anxiety of 4%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…From the study of Alam, Husain and Quarashi, (2017) it was revealed that 16.2% of patients had total burden of miscellaneous Dermatoses, Eczema (27.7%) And Fungal Infections (11.2%). 9 In the study of Ahmed et al majority of the subjects had acne vulgaris (29.5%), followed by atopic dermatitis (22.3%), vitiligo (20.7%) and psoriasis (6.4%); the remainder had other diseases such as alopecia areata, lichen planus or warts. Reported a prevalence of depression of 18% in 50 Alopecia patients and a prevalence of anxiety of 4%.…”
Section: Discussionmentioning
confidence: 94%
“…Association between socio-demographic factors with depression, anxiety, stress found significant association between gender in all studied psychiatric variables. The study of Alam et al (2017) 9 found about half (45.6%) of the patients were females and found to had higher proportion of depression as 27.8%, anxiety as 16.70% and stress as 16.70% while for males' depression observed among 5.1%, anxiety as 17.40% and stress as 1.40% respectively. Wessley et.…”
Section: Discussionmentioning
confidence: 95%
“…Our analysis included 121 studies to calculate the pooled global prevalence of seborrheic dermatitis. These studies encompassed 1 260 163 participants with clinician-diagnosed seborrheic dermatitis, uncovering an overall pooled prevalence of 4.38% (95% CI, 3.58%-5.17%) with an IQR of 1.55% to 5.45%, alongside significant statistical heterogeneity ( I 2 = 99.94%; df = 120; Q = 38 414.25) (Table, Figure 2, Figure 3). Sensitivity analyses confirmed the stability of this prevalence estimate, showing minimal variation in the sequential exclusion of individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the frequency of atopic dermatitis was found to be 4.1% in this study. Alam MN et al, in 2017 though reported it to be 12.4% 21 . In both instances, these differences in results could be attributed to the differences in sample sizes and study settings as both of the later studies were conducted with larger sample sizes and in tertiary care hospitals with potentially different referral patterns.…”
Section: Discussionmentioning
confidence: 96%
“…In our study the frequency of dermatitis was found to be 23.3%. Tameez-Ud-Din BA et al, in 2010 reported the frequency of dermatitis to be 13.9% 13 while Alam MN et al, in 2017 reported the frequency of dermatitis to be only 5.4% among patients attending dermatology OPD 21 . Furthermore, the frequency of atopic dermatitis was found to be 4.1% in this study.…”
Section: Discussionmentioning
confidence: 98%